2013
DOI: 10.1159/000354434
|View full text |Cite
|
Sign up to set email alerts
|

TAZ Mediates Lysophosphatidic Acid-Induced Migration and Proliferation of Epithelial Ovarian Cancer Cells

Abstract: Background: Transcriptional co-activator with PDZ-binding motif (TAZ), a downstream effector of the Hippo pathway, has been reported to regulate organ size, tissue homeostasis, and tumorigenesis by acting as a transcriptional co-activator. Lysophosphatidic acid (LPA) is a bioactive lipid implicated in tumorigenesis and metastasis of ovarian cancer through activation of G protein-coupled receptors. However, the involvement of TAZ in LPA-induced tumorigenesis of ovarian cancer has not been elucidated. Methods: I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 33 publications
(43 reference statements)
1
39
0
Order By: Relevance
“…67 In recent years, emerging evidences showed that LPA also stimulated ovarian cancer cell proliferation and motility via MAPK, CXCL12-CXCR4 axis, TAZ (transcriptional co-activator with PDZ binding motif), and its downstream signaling pathways. 68 Sphingosine kinases 1 (SphK1), one kinase of S1P production, is overexpressed in many types of cancers. It has been reported that crosstalk between LPA/LPA1 and epidermal growth factor receptors (EGFRs) mediated the upregulation of SphK1 to promote cell proliferation and motility in gastric cancer cells and squamous cell carcinoma cell lines of the head and neck.…”
Section: Expression Of Atx/lpa Axis In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…67 In recent years, emerging evidences showed that LPA also stimulated ovarian cancer cell proliferation and motility via MAPK, CXCL12-CXCR4 axis, TAZ (transcriptional co-activator with PDZ binding motif), and its downstream signaling pathways. 68 Sphingosine kinases 1 (SphK1), one kinase of S1P production, is overexpressed in many types of cancers. It has been reported that crosstalk between LPA/LPA1 and epidermal growth factor receptors (EGFRs) mediated the upregulation of SphK1 to promote cell proliferation and motility in gastric cancer cells and squamous cell carcinoma cell lines of the head and neck.…”
Section: Expression Of Atx/lpa Axis In Cancermentioning
confidence: 99%
“…The coadministration of inhibitor to the ATX/LPA axis with sunitinib would prolong the sensitivity of renal cell carcinoma to sunitinib in the xenograft model. 68 A recent research has shown that LPA signaling increased Nrf2 transcription factor stability and nuclear localization, and further increased transcription of multidrug-resistant transporters and antioxidant genes, which protected cells from chemotherapy-induced death. 95 In recent years, the role of the ATX/LPA axis in cancer resistance to radiotherapy has also emerged.…”
Section: Expression Of Atx/lpa Axis In Cancermentioning
confidence: 99%
“…In ovarian CSCs, YAP promotes ovarian CSC tumorigenesis and regulates CSC self-renewal and differentiation [26,27]. The transcriptional co-activator with PDZ-binding motif (TAZ) is a transcriptional effector of the Hippo signaling cascade and regulates cell proliferation and tumorigenesis [21,28,29]. In addition, previous studies have shown that YAP acts as an oncogene in a subtype of breast CSCs and lung CSCs, thus serving as a good target for molecular therapies against cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Two subsequent studies further confirmed the stimulation of YAP/ TAZ by LPA in ovarian cancer cells [39,40]. Cai and Xu [39] showed that LPA induced YAP dephosphorylation and nuclear localization in dose and time-dependent manner in several ovarian cancer cell lines.…”
Section: Introductionmentioning
confidence: 76%
“…Finally, they observed that the phosphorylation level of YAP was reduced in epithelia ovarian cancer (EOC) specimens compared with normal or benign ovarian tissues, supporting that the phosphorylated YAP could serve as a biomarker for EOC [39]. Jeong et al [40] also found that the activation of TAZ by LPA treatment could be blocked by specific LPA receptor inhibitor Ki16425 or siRNA target LPA1, and TAZ is required for LPA-induced ovarian cancer cell migration. These two studies strengthened the potential role of LPA in regulating YAP/TAZ in cancer cells and indicated that this axis may play crucial role in numerous cancer types.…”
Section: Introductionmentioning
confidence: 94%